Comparative growth performance of Kappaphycus striatus and the green variety of Kappaphycus alvarezii under longline cultivation - Muzahar, Muzahar; Raza’I, T. Said; Viruly, Lily; Wulandari, Rika; Miranti, Shavika; Putri, Dwi Septiani; Yulianto, Tri; Bakkara, Okto Rimandi; Irawan, Henky; Sinaga, Daniel; Nasmi, Jannesa; Andia, Bherly; Saputra, Rio; Bahri, Samsul; Lovina, Ronaldy; Darmawan, David; Syafiq, R. Muhammad (Universitas Malikussaleh, 2025)
This study compares the growth of two seaweed species, Kappaphycus striatus and Kappaphycus alvarezii (green variety), using the longline method in the waters of Pelakak Village, Lingga Regency. This research aims to identify differences in daily growth rates and environmental factors affecting the productivity of both seaweed species. The study was conducted over 45 days using a randomized block design with two treatments and four replications. Measured parameters included absolute weight growth, specific growth rate, and water quality. The results showed that K. alvarezii (green variety) exhibited a higher daily growth rate (0.55% weight/day) compared to K. striatus (0.31% weight/day). Environmental factors such as temperature (28–30°C), salinity (30–31 ppt), and pH (7.1–7.4) were within the optimal range, but the current velocity (0.4–0.5 m/s), which exceeded the standard, potentially inhibited growth an increased the risk of talus damage. The t-student test indicated no significant difference in growth between the two seaweed species (p>0.05). These findings suggest that K. alvarezii (green variety) is more adaptive to local environmental conditions than K. striatus, although current velocity and pest presence remain challenges in seaweed cultivation. This study contributes to optimizing seaweed farming strategies in coastal areas. Keywords: Growth; Kappaphycus striatus; Kappaphycus alvarezii Green Variety; Longline